ANALISIS PENGARUH GAME ONLINE DAN MOTIVASI BERMAIN TERHADAP MINAT BELAJAR SISWA SD - Hendi Sama; Jevon Junanto (JURNAL ILMIAH BETRIK, 2022)
This study aims to determine the effect of online game and gaming motivation on elementary students' learning interest. This study uses a qualitative and quantitative approach with the variables of Online Game and Gaming Motivation as independent variables and Learning Interest as the dependent variable. In the qualitative method, 30 samples of elementary school students were taken and in the quantitative method, 392 samples of elementary school students were taken with the population number set at 20,000, due to the absence of a specific number. Interviews were conducted as a data collection technique with a qualitative approach, while the quantitative approach was carried out by distributing questionnaires. Data analysis in both methods was carried out using the SPSS application, specifically for the qualitative approach which was codified beforehand. Based on the results of qualitative and quantitative data analysis, the authors conclude that the variables of Online Game and Gaming Motivation partially and simultaneously have a significant effect on the Learning Interest variable with an effect of 59.9% and 52.2% respectively